2013
DOI: 10.5152/jaem.2011.064
|View full text |Cite
|
Sign up to set email alerts
|

The Disease that is Unforgettable: a Case of Rapidly Progressive Tetanus

Abstract: GirişTetanoz, şiddetli solunum sıkıntısı ve persistan tonik spazmlarla karakterize, akut seyirli bir santral sinir sistemi enfeksiyonudur (1). Sporları, insan ve hayvanların intestinal sisteminde ve toprakta bulunan Clostridium tetani'nin toksinleri hastalığa neden olur. Aktif immü-nizasyon programlarına rağmen gelişmekte olan ülkelerde mortalite hızı yüzbinde 28'dir (1, 2). Doğumdan önce bakım hizmetlerinin sınırlı verildiği, uygun olmayan ortamlarda doğumların yaptırıldığı ülkelerde yenidoğanlar için neonata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
0
0
Order By: Relevance
“…The emergency department is a hectic place [19], and this can make obtaining detailed medical histories a challenging task. In the tetanus case report by Koruk et al, despite seeking medical help from various physicians, the patient was ultimately referred to the psychiatry clinic [20]. We believe that improving the knowledge level of healthcare personnel regarding tetanus will contribute to a decrease in tetanus cases.…”
Section: Discussionmentioning
confidence: 94%
“…The emergency department is a hectic place [19], and this can make obtaining detailed medical histories a challenging task. In the tetanus case report by Koruk et al, despite seeking medical help from various physicians, the patient was ultimately referred to the psychiatry clinic [20]. We believe that improving the knowledge level of healthcare personnel regarding tetanus will contribute to a decrease in tetanus cases.…”
Section: Discussionmentioning
confidence: 94%
“…[14] Adult tetanus cases, however, are still being reported in our country. [15][16][17][18][19] Apart from the theses conducted in our country, other tetanus studies were examined, and it was found that seroprevalence and immunity studies were found in the local literature. [20][21][22][23] There are also studies that evaluate knowledgeopinion-attitude about tetanus vaccination.…”
Section: Discussionmentioning
confidence: 99%